Uncertainty in Pharmacology Epistemology, Methods and Decisions - La Caze, Adam; Osimani, Barbara (Boston Studies in the Philosophy and History of Science, 2020)
This volume covers a wide range of topics concerning methodological, epistemological, and regulatory-ethical issues around pharmacology. The book focuses in particular on the diverse sources of uncertainty, the different kinds of uncertainty that there are, and the diverse ways in which these uncertainties are (or could be) addressed. Compared with the more basic sciences, such as chemistry or biology, pharmacology works across diverse observable levels of reality: although the first step in the causal chain leading to the therapeutic outcome takes place at the biochemical level, the end-effect is a clinically observable result-which is influenced not only by biological actions, but also psychological and social phenomena. Issues of causality and evidence must be treated with these specific aspects in mind. In covering these issues, the book opens up a common domain of investigation which intersects the deeply intertwined dimensions of pharmacological research, pharmaceutical regulation and the related economic environment. The book is a collective endeavour with in-depth contributions from experts in pharmacology, philosophy of medicine, statistics, scientific methodology, formal and social epistemology, working in constant dialogue across disciplinary boundaries.